Web-Based Expert System Detects Malnutrition in Toddlers with the Naïve Bayes Method - Rifki Nur Apriyono; Agung Triayudi; Ira Diana Solihati (Institute of Computer Science (IOCS), 2020)
Nutrition is the supply of ingredients or food that both organisms and cells in the human body need to be able to: survive. While in the field of science and medical, nutrition may refer to: the science or practice of consumption as well the use of food. Malnutrition is a technical term commonly used in: nutrition, health, and medicine circles. Malnutrition: the condition of a person whose nutrition is below average. Symptoms of malnutrition can also be felt with following characteristics such as: fatigue, loss of appetite, impaired vision, growth and poor intellectual development too. According to the Basic Health Research in 2018, the percentage of the number of malnourished toddlers in Indonesia is: as much as 3.9% and malnutrition is: 13.8%. This study aims to detect malnutrition aged 1-5 years (toddler). This research uses: the Naïve Bayes method. In this study, there're known to be types of disease based on the symptoms, namely: Kwarshiorkor (P1), Marasmik-Kwarshiorkor (P2), Marasmus (P3) with 24 symptoms of malnutrition. With this research, it is expected to: help in the prevention of diseases and minimize the symptoms of malnutrition in toddlers.